1995
DOI: 10.1111/j.1600-0560.1995.tb00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation markers in predicting metastases in malignant melanoma

Abstract: It is often difficult to predict the outcome of melanoma in patients with Clark level III-IV disease. We sought to identify markers of cell proliferation which may be useful in predicting prognosis. Patients with Clark's level III-IV malignant melanoma who had no local recurrences or metastases were matched with patients of comparable level and thickness who did experience recurrences of metastases. Cell proliferation markers p53, proliferating cell nuclear antigen (PCNA), and Ki-67 were assessed by immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 25 publications
1
18
1
1
Order By: Relevance
“…In addition, immunostaining for Ki-67 antigen is helpful in identifying individuals with thick nodular melanomas who are at risk of metastatic disease (Vogt et al, 1997). PCNA expression in cutaneous melanomas seems to be a marker of tumour progression (Takahashi et al, 1991;Evans et al, 1992), but it may not help in predicting prognosis in these tumours (Reddy et al, 1995). AgNOR counts often correlate with other markers of cell proliferation, but the staining techniques and the counting methods suffer standardization problems (Cross and Start, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, immunostaining for Ki-67 antigen is helpful in identifying individuals with thick nodular melanomas who are at risk of metastatic disease (Vogt et al, 1997). PCNA expression in cutaneous melanomas seems to be a marker of tumour progression (Takahashi et al, 1991;Evans et al, 1992), but it may not help in predicting prognosis in these tumours (Reddy et al, 1995). AgNOR counts often correlate with other markers of cell proliferation, but the staining techniques and the counting methods suffer standardization problems (Cross and Start, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…57,62,[67][68][69] Many studies have shown an increase in recurrence rate and mortality that directly correlates with increasing positivity for Ki-67; however, others have shown that this correlation is not independent of Breslow thickness. 60,61,63,[69][70][71][72][73] Reddy et al 74 did not find any correlation at all, although they only studied 14 cases.…”
Section: Markers Of Tumor Cell Proliferationmentioning
confidence: 99%
“…56,76,77 Niezabitowski et al found increased PCNA expression to be an independent prognostic factor for increased mortality and decreased diseasefree survival, although others have been unable to confirm this finding. 72,74,75,78 Cyclins Cyclins are proteins, approximately 100 amino acids long, which bind and activate cyclin dependent kinases causing the cell to progress through the various stages of the cell cycle. 63,65,[79][80][81] Cyclins C, D1, D2, D3 and E help the cell progress from G 1 to S phase; cyclin A from S to G 2 phase; cyclin B from G 2 to mitosis.…”
Section: Markers Of Tumor Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…70 One study of level III and IV melanomas found no correlation of survivorship with PCNA or Ki-67 expression; however, in that study, flow cytometric analysis showing an aneuploid DNA content was associated with a higher risk of metastatic progression. 71 …”
Section: Mitotic Ratementioning
confidence: 99%